Administration of stable iodine to the population around the Chernobyl nuclear power plant - Mettler, F; Royal, H; Hurley, JR; Khafagi, F; Sheppard, M; Beral, V; Reeves, G; Saenger, E; Yokoyama, N; Parshin, V; Griaznova, E; Taranenko, M; et al. (1992)
A very large amount (2.5 x 1017 Bq) of radioactive iodine was released as a result of the Chernobyl accident in 1986. An effective protective action that may be employed to reduce the potential radiation dose to the thyroid gland after a serious nuclear reactor accident is the administration of stable iodide in the form of potassium iodide (KI). Potassium iodide was reportedly given to nearly five and a half million persons after the Chernobyl accident. During the International Chernobyl Project, medical investigators asked the general population in both highly contaminated and control settlements about thyroid prophylaxis. Only 25% of persons currently living in the most contaminated regions reported taking potassium iodide. Sixty-six percent indicated that they did not take potassium iodide and 9% were uncertain. Of those who took stable iodine prophylactically. 44% indicated that it was in solution, 44% that it was in tablets and 12% did not remember how it was administered. Only about one third of persons were able to indicate the duration of time that they took such medication. The average was 6.2 days. It appears that iodine prophylaxis will not have a major impact on estimated collective thyroid doses to the general population living around the Chernobyl nuclear power plant. The impact that distribution of KI had upon the plant and emergency accident workers remains unknown to us.